2018
DOI: 10.18203/2349-2902.isj20180357
|View full text |Cite
|
Sign up to set email alerts
|

Mass closure versus layered closure of midline laparotomy incisions: a prospective comparative study

Abstract: Background: The ideal method of abdominal wound closure remains to be discovered. It should be technically so simple that the results are as good in the hands of a trainee as in those of the master surgeon. The best abdominal closure technique should be fast, easy, and cost effective while preventing both early and late complications. Present study is undertaken to compare the two methods (Mass closure and Layered closure) of laparotomy wound closure in relation to post-operative complications, time for wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
5
1
0
Order By: Relevance
“…It was observed that mean wound closure time was significantly less in mass closure group as compared to layered closure group (p < 0.001). Similar study was done by Deshmukh et al (2018) [17] and Kendall et al (1991) [18], they reported mean wound closure time in mass closure group was 16.2 minutes and 18 minutes respectively which were consistent with this current study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was observed that mean wound closure time was significantly less in mass closure group as compared to layered closure group (p < 0.001). Similar study was done by Deshmukh et al (2018) [17] and Kendall et al (1991) [18], they reported mean wound closure time in mass closure group was 16.2 minutes and 18 minutes respectively which were consistent with this current study.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study post-operative wound infection rate was relatively high in Group A patients than Group B patients. We found, wound infection rate in mass closure group was 10% which was comparable with previous studies [17] [19]. On the other hand wound infection rate in layered closure group was 30.0% in this study, which was higher as compared to the previous studies [18] [20] [21].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…11 There was a male predominance with a M: F ratio of 2.84: 1. Similar male predominance in patients undergoing laparotomy was reported by Simpson et al and Deshmukh et al 12,13 In contrast to above studies the authors such as Singh et al reported a female predominance (1:2) in patients undergoing nontraumatic emergency laparotomy. 14 In our studies the other factors such as body mass index, serum albumin, total serum protein, hemoglobin and mean age of the affected cases was found to be comparable with no statistically significant difference (p>0.05).…”
Section: Discussionsupporting
confidence: 65%
“…A study by Israelsson et al; [10] and has also shown the rate of infection to be 7% in their study [9 of 2340]. In comparison to mass closure the wound infection in the present study was lesser in the layered closure in contract Deshmukh SN et al; [17] have found higher infection rates in layered closure when compared to mass closure. The difference could be because of the patient factors in wound healing.…”
Section: Discussionsupporting
confidence: 53%